Faktor-Faktor Bauran Pemasaran yang Mempengaruhi Loyalitas Pelanggan Berdasarkan Aspek-Aspeknya - Mustati' Uliyah; Lisa Sulistyawati (LPPM Institut Nasional Laa Roiba Bogor, 2022)
This study aims to determine the effect of product, price, promotion, distribution, people, process, and physical evidence on customer loyalty, either partially and simultaneously. The population in this study are GoFood customers in Gresik who are limited by certain criteria. The sample used in this study was 100 respondents using a non-probability sampling technique with a purposive sampling approach. Collecting data in this study using a questionnaire via google form. The data testing methods used are Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, T Test, and F Test. Based on the results of the study, it can be seen that the results of this study indicate that the variables of Price, Promotion, Distribution, Process, Physical Evidence partially have a significant effect on Customer Loyalty. Product and Person variables partially have no significant effect on Customer Loyalty. Then the variables of Product, Price, Promotion, Distribution, People, Process, and Physical Evidence simultaneously have a significant effect on customer loyalty.